Advances in dermatological application of GelMA hydrogel microneedles. Issue 4 (16th April 2023) - Li, Hongyang; Li, Jiayi; Xu, Jingjing; Li, Lingjun; Wang, Yurong; Liu, Chunhui; Zhou, Jia
Abstract: Background: Compared with systemic administration methods like injection and oral administration, traditional transdermal drug delivery has the advantages of rapid onset of activity and low side effects. However, hydrophilic drugs and bioactive substances are often unsuitable for traditional transdermal drug delivery. Methods: The application of microneedles made from gelatin methylacryloyl (GelMA) has greatly expanded thepossibilities for skin transdermal drug delivery. We have reviewed the latest literatures about the dermatological application of GelMA hydrogel microneedles in recent years using Google Scholar, PubMed and Springer. Results: GelMA hydrogel microneedles exhibit huge potency in the diagnosis and treatment of skin diseases, and this technology also brings broad application prospects for subcutaneous micro‐invasive transdermal targeted drug delivery, which mainly used in skin tissue fluid collection, local substance delivery and wound healing. Conclusion: With in‐depth research on GelMA hydrogel, this technology will bring more breakthroughs and developments in the clinical diagnosis and treatment of skin diseases.